A földhasználat és a kultúra kapcsolata, avagy a kultúramarketing és a kultúrafogyasztás kialakulásának állomásai - Fehér, Euridiké (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
Agriculture and farming created special traditions which have transformed into popular costums and believes during centuries and changing nations’ cultural consumption remarkably. The change and spread of our culture itself and culture consumption is not only an ethnical and sociological question but also an economic one. This is the reason why I think it is important to define the culture in the aspect of the economy as due to it we can form different culture consuming groups. I denominate three of the most important directions and dimensions according to the bibliography processed until now. These are the following: traditional, autonomous and heteronomous cultural dimensions. The first step of my research is to expound the possible consumers of these dimensions mentioned above, the permeability between dimensions or their exclusivity if there is any. At the end of the day I would like to show the new challenges and possible solutions of culture marketing considering the categories defined by me in the meantime.